Gender Dynamics and Women's Economic Contributions in The Informal Economy within The Context of Islam and Multicultural Societies - Makka, Misbahul Munir; Abasi, Masyrifah; Lajilu, Fatta; Purwanto, Irzal; Bukido, Rosdalina; Suleman, Nenden Herawaty; Nagauleng, Andi Mukarramah; Bhatti, Muhammad Safdar; Gómez, José Manuel Naranjo (Kawanua International Journal of Multicultural Studies, 2024)
In the evolving landscape of global economics, the significant role of women in the informal economy, particularly housewives, remains underexplored. This study examines the gender dynamics and economic contributions of housewives in the informal economy, focusing on the context of Islamic values and multicultural societies in Poigar Village. Using a qualitative approach, this research delves into how housewives balance domestic responsibilities and economic activities, particularly through cake sales, to enhance family well-being. Key findings highlight the motivations driving housewives to engage in informal economic activities, such as economic necessity, skill utilization, and the pursuit of financial independence. Additionally, these activities are shown to significantly improve family income, enhance financial stability, and foster social recognition. From an Islamic perspective, these efforts align with principles of family cooperation, economic empowerment, and spiritual reward. The study underscores the importance of policies that support women in informal economies, such as access to capital, skill training, and social acknowledgment of their contributions. Future research should explore broader and more diverse samples to generalize findings and examine the long-term impacts of women's economic participation in similar contexts.